2011
DOI: 10.1016/j.actamat.2010.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties at different length scales and strain rates of nanocrystalline tantalum produced by high-pressure torsion

Abstract: Wei, Q.; Pan, Z. L.; Wu, X. L.; Schuster, B. E.; Kecdkes, L. J.; and Valiev, R. Z., "Microstructure and mechanical properties at different length scales and strain rates of nanocrystalline tantalum produced by high-pressure torsion" (2011 AbstractFully dense, nanocrystalline tantalum (average grain size as small as $40 nm) has been processed for the first time by high-pressure torsion. High-resolution transmission electron microscopy reveals non-equilibrium grain boundaries and grains decorated with high-dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(34 citation statements)
references
References 96 publications
1
31
1
1
Order By: Relevance
“…The Vickers hardness at the saturated level (HV) of a wide range of pure metals and semi-metals with various crystal structures processed through severe plastic deformation (SPD) have been reported [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]28,66]. In this work, we study the increment of hardness (∆HV) of 17 high purity (better than 99.9%) elements due to HPT reported in [4,5,9,10,23,28,66] (see Table 1).…”
Section: Hardness Data Of Hpt Processed Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vickers hardness at the saturated level (HV) of a wide range of pure metals and semi-metals with various crystal structures processed through severe plastic deformation (SPD) have been reported [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]28,66]. In this work, we study the increment of hardness (∆HV) of 17 high purity (better than 99.9%) elements due to HPT reported in [4,5,9,10,23,28,66] (see Table 1).…”
Section: Hardness Data Of Hpt Processed Metalsmentioning
confidence: 99%
“…Following extensive work in the field by a range of researchers, extensive data on the hardness and microstructure of HPT processed metals and alloys is now available (e.g. [4,5,6,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]). Data on hardness increase due to HPT have been published for over 20 pure metals, and several of the factors influencing the hardness of HPT processed pure metals have been investigated in some detail by Edelati and Horita [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that BCC metals exhibit an increased propensity to ASB when their grain sizes are reduced into the ultrafine-grain and nano-crystalline regime [2]. This is attributed to the associated changes in the strength, strain hardening behaviour and strain rate sensitivity when the grain size changes [2]. Also, it has been observed that the ASBs associated with FCC metals, such as aluminium and copper, are diffused and exhibit a plastic flow phenomenon [3].…”
Section: Introductionmentioning
confidence: 95%
“…Mechanical and material factors have been reported to influence the appearance and susceptibility of materials to the formation of ASBs [1]. It has been reported that BCC metals exhibit an increased propensity to ASB when their grain sizes are reduced into the ultrafine-grain and nano-crystalline regime [2]. This is attributed to the associated changes in the strength, strain hardening behaviour and strain rate sensitivity when the grain size changes [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the strain-rate sensitivity of BCC metals was found to decrease with the reduction in grain size, especially in the ultrafine-grained and nanocrystalline regimes. [1,[11][12][13] To understand this trend, Wei et al [11,12] used the m ∼ 1/ √ τ scaling relation to explain the grain size effect on m based on the HallPetch-type elevation of the flow stress (τ ) at small grain sizes. More recently, Cheng et al [2] proposed an alternative explanation.…”
mentioning
confidence: 99%